Alpha-Actinin-3 (ACTN3) R/X Gene Polymorphism and Physical Performance of Multi-Ethnic Malaysian Population - Ahmad Yusof, Hazwani; Singh, Rabindarjeet; Zainuddin, Zafarina; Rooney, Kieron; Che Muhamad, Ahmad Munir (Asian Exercise and Sport Science Association, 2016)
A disparity population data set in the current literature with limited reports among Asian samples and the inconsistent findings among different ethnic groups warrant further investigation on the association between alpha-actinin-3 (ACTN3) R/X gene polymorphism and human physical performance in Asian population. This study was designed to examine the association between ACTN3 R/X gene polymorphism and physical performance of multi-ethnic Malaysian population. One hundred eighty well-trained athletes (34 endurance, 41 strength, and 105 intermittent) and 180 controls were drawn from four ethnic groups in Malaysia (Malay, Chinese, Indian, and Other Bumiputra). A sample of deoxyribonucleic acid (DNA) was retrieved from a buccal swab from each participant and the ACTN3 R/X genotype was identified through polymerase chain reaction and restriction fragment length polymorphism analysis. The strength and endurance performances of the athletes were evaluated with maximal voluntary contraction and Yo-Yo intermittent recovery level 2 tests, respectively. The independent t-test, chi-square, multivariate, and one-way analysis of variance were used for data analysis. ACTN3 R/X alleles (p = 0.672) and genotype (p = 0.355) frequencies did not vary much between the multi-ethnic groups of Malaysian athletes. These small variations did not have any influence on handgrip strength (p = 0.334), leg strength (p = 0.256), and Yo-Yo intermittent recovery level 2 performance (p = 0.425) between these ethnic groups. The RR and XX genotypes were more frequent among strength and intermittent athletes, respectively. Athletes with the RR genotype had greater handgrip than those with the RX genotype (p = 0.031), but not different from athletes with the XX genotype (p = 0.228).